2011
DOI: 10.1519/jsc.0b013e3181e06ef8
|View full text |Cite
|
Sign up to set email alerts
|

Jump Peak Power Assessment Through Power Prediction Equations in Different Samples

Abstract: The aim of this study was to describe the characteristics of jump capacity in a group of secondary school students and to develop 2 specific equations-applied to boys and girls, respectively, to estimate the jump power of secondary school students. Four hundred and fifty-six boys (age, 14.1 ± 0.8 years; mass, 61.9 ± 15.7 kg; height, 1.64 ± 0.10 m) and 465 girls (age, 14.1 ± 0.9 years; mass, 55.1 ± 10.0 kg; height, 1.58 ± 0.07 m), all of them secondary school students, volunteered to participate in this study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 15 publications
1
23
0
2
Order By: Relevance
“…In this sense, this method allows the estimation of the height of the jump based on the body mass and time of the aerial phase (Bosco et al ., ; Garcia‐Lopez et al ., ; Dias et al ., ). It is also possible to estimate the power of the lower limb from mathematical equations (Sayers et al ., ; Lara‐Sanchez et al ., ). However, some differences (i.e.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In this sense, this method allows the estimation of the height of the jump based on the body mass and time of the aerial phase (Bosco et al ., ; Garcia‐Lopez et al ., ; Dias et al ., ). It is also possible to estimate the power of the lower limb from mathematical equations (Sayers et al ., ; Lara‐Sanchez et al ., ). However, some differences (i.e.…”
Section: Introductionmentioning
confidence: 97%
“…In this sense, this method allows the estimation of the height of the jump based on the body mass and time of the aerial phase (Bosco et al, 1983;Garcia-Lopez et al, 2005;Dias et al, 2011). It is also possible to estimate the power of the lower limb from mathematical equations (Sayers et al, 1999;Lara-Sanchez et al, 2011). However, some differences (i.e.~5%) in the evaluation by force platforms and contact mats have been reported (Aragon Vargas, 2000;Garcia-Lopez et al, 2005;Moir et al, 2008b;Boullosa et al, 2011;Dias et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Quagliarella et al [40] performed a detailed comparative study of several equations, and reported very high error values (>50%) and concluded that the use of Pmax estimates, can only be useful to compare the performance of groups of subjects. Discrepancies and equation-dependant accuracy of prediction were also observed in other comparative studies [8,36,41,42], making the use of regression-based estimates irrelevant for an individually accurate determination of lower limb Pmax.…”
Section: 1mentioning
confidence: 78%
“…Numerous regression equations have been published to estimate Pmax (e.g. [34][35][36][37][38][39]). However, although practical, this estimation method has several major limitations.…”
Section: 1mentioning
confidence: 99%
“…One study examined the precision of various power equations using the vertical jump height and peak power measured by a force plate, and then compared to estimated peak power equations with over 800 secondary school students. In this study, the Harman equation was found to be precise, reaching 3.6-4.1 % accuracy [53].…”
Section: Countermovement Vertical Jumpmentioning
confidence: 59%